Building moderate Muslim networks - Rabasa, Angel (Rand Corporation monograph series., 2007)
Radical and dogmatic interpretations of Islam have gained ground in recent years in many Muslim societies via extensive Islamist networks spanning the Muslim world and the Muslim diaspora communities of North America and Europe. Although a majority throughout the Muslim world, moderates have not developed similar networks to amplify their message and to provide protection from violence and intimidation. With considerable experience fostering networks of people committed to free and democratic ideas during the Cold War, the United States has a critical role to play in leveling the playing field for Muslim moderates. The authors derive lessons from the U.S. and allied Cold War network-building experience, determine their applicability to the current situation in the Muslim world, assess the effectiveness of U.S. government programs of engagement with the Muslim world, and develop a "road map" to foster the construction of moderate Muslim networks